Os conflitos violentos de bullying na escola e seus entrelaçamentos com a justiça restaurativa - Louzada, Marcelle Cardoso (2013)
The present dissertation, a prerequisite for the conclusion of the Master in Education at the Postgraduate Program in Education of the Federal University of Santa Maria, is tied to the research line: School Practice and Public Policy. This is a qualitative-quantitative research, a case study type. Portrays the violent conflicts of bullying at school and their entanglements with the Restorative Justice. Aims at understanding how violent conflict are presented in school and the characteristics that define the practice of bullying, its characters and forms of intervention. Raises the issue of judicialization of school conflicts and the existence of another lens for conflictive resolution under the restorative bias. Presents Restorative Justice, its application in Brazil and structure of the Restorative Circles. Through research, it was found that Restorative Justice favors the performance of teachers and students, as a useful tool in confronting and preventing violent conflict of bullying at school.